Student Worksheets Assisted by Augmented Reality on Critical Thinking Skills in High School Physics: Study of Teacher Perceptions in Indonesia - Anggraini, Aisyah; Siahaan, Sardianto Markos; Fathurohman, Apit (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2024)
This study is classified as a quantitative descriptive research. The objective of this study is to assess the necessity of utilizing Augmented Reality to support student workbooks in high school physics, with a specific focus on enhancing critical thinking abilities. The research employed a purposive sample methodology as the sampling method. The study topic survey employed a questionnaire as the instrument. The researcher given a Google form link to post this questionnaire, which was then completed online within a defined timeframe. This research focuses on high school physics teachers in Indonesia, specifically those located in 17 provinces including Aceh, North Sumatra, Riau, Jambi, South Sumatra, Lampung, Bengkulu, Banten, West Java, Central Java, East Java, DIY, West Kalimantan, Central Kalimantan, NTT, Maluku, and Southwest Papua. The research study had a total of 84 participants. The research findings indicate that (1) 49% of high school students demonstrate a high level of critical thinking skills in physics subjects; (2) 91% of high school teachers utilize student worksheet in physics instruction; (3) There is a 93% demand for incorporating student worksheet assisted by Augmented Reality in physics learning; and (4) 42% of teachers prefer student worksheet in a printed format. According to this study, there is a requirement for student worksheets supported by Augmented Reality in physical format to enhance students' ability to think critically during the process of studying physics. This first investigation will be extended into further research with the aim of creating student workbooks supported by Augmented Reality to enhance critical thinking abilities in relation to the subject of impulse and momentum.